Deleuze and The Fold: A Critical Reader
XII, 263 p.
Keywords: Featuring contributions by leading academics this collection is a companion to one of the most intricate of Deleuze's philosophical texts, articulating Leibnizian thought within the context of Baroque expressionism, characterized by its interdisciplinary approach to philosophy. This reader offers an incisive critical overview of its key themes.